Charybdis moretonensis Rees & Stephenson, 1966, a junior syno-nym of Charybdis granulata (de Haan, 1833) (Crustacea: Decapoda: Brachyura) - Ahyong, Shane T.; Lee, Timothy (Zootaxa, 2005)
Charybdis moretonensis Rees & Stephenson, 1966, is known only from the holotype and has been suspected to be conspecific with C. granulata (de Haan, 1833). Comparison of the holotype of C. moretonensis with a large series of C. granulata from Australia and various Indo-Pacific localities showed that the two nominal species are morphologically indistinguishable. Characters thought to distinguish the two species are not reliable, being based on a misinterpretation of the damaged holotype of C. moretonensis, the incomplete type description of C. beauforti Leene & Buitendijk, 1949 (= C. granulata), and a failure to account for allometric variation. Therefore, C. moretonensis is synonymised with C. granulata. We also report the largest known specimen of C. granulata and confirm its presence in eastern Australia.